Pemodelan dan Analisis Proses Bisnis untuk Layanan Seleksi Mandiri Penyandang Disabilitas pada Pusat Layanan Disabilitas UB - Nadiyah Hasnada; Ismiarta Aknuranda; Alies Poetri Lintangsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Brawijaya University's Center for Disability Services (PLD UB) is an organization in Universitas Brawijaya that is focused in providing academic and non-academic services to students with disabilities in Universitas Brawijaya. One of their services is Selection for Student Candidates with Disabilities (SMPD) that is held periodically, once a year. There are processes that can still can be improved upon. Therefore, designing business process architecture is done to help PLD UB in evaluating SMPD so they can provide better services. In this undergrad thesis, Business Process Management framework is used to design the business process models, and is conducted up to the business process analysis. In identifying the core business process, researcher did an interview with SMPD committees and discovered six core business processes, which are SMPD announcement publishing, enrollment, personal data submission, administration selection, psychological test and general knowledge selection, and interview selection. All six processes then modeled into six business process models using Business Process Modeling Notation, abbreviated as BPMN. And on the analysis process, Root Cause Analysis with Why-why Diagram is used on each business processes. After analysis is conducted, there are total of twelve issues that emerges from all six business processes which, most of them, are related to efficiency of technical aspects in SMPD.